Implementing the IMB model combined with rehabilitation nursing to promote rehabilitation and self-management in coronary heart disease patients - Jinjin Gong; Xinmei Zhang (Frontiers in Cardiovascular Medicine, 2026)
Objective To examine the association between routine Information-Motivation-Behavioral Skills (IMB) model-based rehabilitation nursing and rehabilitation-related outcomes and self-management behaviors in patients with coronary heart disease (CHD). Methods This single-center retrospective cohort study included 150 patients with CHD admitted to Shandong Provincial Third Hospital from January 2024 to February 2025. After ethics approval, data were extracted from existing clinical and nursing records. Patients were retrospectively classified into a treatment group (documented IMB model combined with rehabilitation nursing, n = 75) and a control group (documented conventional care, n = 75) according to the nursing care recorded in the source documents. Propensity score matching was used to balance baseline characteristics between the two groups. Repeatedly measured outcomes were analyzed using repeated-measures models, and effect estimates were reported with 95%CIs. Results At the 3-month follow-up, the treatment group showed more favorable 6MWD and LVEF than the control group. Cardiac-related parameters, including interventricular septal thickness, left atrial diameter, aortic dilation, and aortic atherosclerosis, were lower in the treatment group. CQQC scores at 1, 2, and 3 months were higher in the treatment group, and repeated-measures analysis indicated a more favorable quality-of-life change pattern over time. The total CSMS score was higher in the treatment group than in the control group (95.86 ± 4.31 vs. 91.14 ± 4.17; P < 0.001). Emotional management and disease medical management subscale scores were also higher, whereas the difference in daily management was not statistically significant. Treatment adherence was higher in the treatment group than in the control group (90.67% vs. 69.33%), and SAQ domain scores were also more favorable in the treatment group. Conclusion In this retrospective cohort study, the IMB model combined with rehabilitation nursing was associated with more favorable cardiac function, cardiac-related indicators, self-management ability, treatment adherence, and quality-of-life outcomes in patients with CHD. These findings should be interpreted as observational associations and require confirmation in future prospective studies.